2020
DOI: 10.4047/jap.2020.12.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal discrepancy in metal frameworks fabricated by sintering-based computer-aided manufacturing methods

Abstract: The aim of this in vitro study was to evaluate the effect of sintering procedures on marginal discrepancies of fixed partial metal frameworks fabricated using different sintering-based computer-aided design and computer/aided manufacturing (CAD/CAM) techniques. MATERIALS AND METHODS. Forty resin die models of prepared premolar and molar abutment teeth were fabricated using a three-dimensional (3D) printer and divided into four groups (n = 10) according to the fabrication method of metal frameworks used: HM (vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…9 An excellent marginal adaptation is one of the most significant factors for long-term success. 3,[10][11][12][13][14] McLean and von Fraunhofer 15 reported that a gap of 120 µm is acceptable and marginal discrepancies (MD) of less than 80 µm are too difficult to detect in clinical situations. However, there are studies in the literature reporting that the maximum MD of 100 µm 16 and even 50 µm 17 is ideal for the success and longevity of indirect restorations.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 An excellent marginal adaptation is one of the most significant factors for long-term success. 3,[10][11][12][13][14] McLean and von Fraunhofer 15 reported that a gap of 120 µm is acceptable and marginal discrepancies (MD) of less than 80 µm are too difficult to detect in clinical situations. However, there are studies in the literature reporting that the maximum MD of 100 µm 16 and even 50 µm 17 is ideal for the success and longevity of indirect restorations.…”
Section: Introductionmentioning
confidence: 99%
“…19 The direct vision technique is one of the most widely used methods. 3,12,[19][20][21] The traditional way of fabricating metal frameworks, the lost wax casting (LW), is a complex and time-consuming technique. However, computer-aided design/computer-aided manufacturing (CAD/CAM) has gained popularity in dental practice.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations